Analisis Desain Agribisnis Sagu di Kabupaten Konawe Selatan - Muhamad Israh; Idrus Salam; Ine Fausayana (Jurnal Sosio Agribisnis, 2020)
The aims of this study is to analyze: types of processed sago products to be prioritized,  potential of sago agribusiness, and sago agribusiness design. The study was conducted in Konawe Selatan Regency, Southeast Sulawesi Province. Research respondents consisted of district government apparatus, sub-district government, village government, and farmer groups. The analysis method uses the analysis of Revenue Analysis, Exponential Comparison Matrix (MPE), and Analytical Hierarchy Process (AHP). The results of the study revealed that the highest income was obtained by the aci sago processor, amounting to Rp 3,123,750 per month. Sago agribusiness design is carried out by determining priority sago products and then analyzing criteria and alternative priorities for sago agribusiness. Based on the results of the analysis, aci sago is a priority product with a value of 1,572, and the priority criteria are marketing development with a value of 0.558. The alternative priority for sago agribusiness in South Konawe Regency is strengthening capital with a value of 0.205, then followed by developing partnerships with a value of 0,199 and developing technology with a value of 0,195.Keywords: priority; design; agribusiness; sago